Evaluation of Copper removal from industrial sewages by the Green microalgae Chlorella vulgaris - M Malakootian; Z Yousefi; Z Khodashenas Limoni (مجله دانشگاه علوم پزشکی گرگان, 2016)
Background and Objective: Bioabsorbat is one of the most effective methods for the removal of heavy metals from industrial sewages. This study was done to assess the evaluation of Copper removal from industrial sewages by the Green microalgae Chlorella vulgaris.